Response of Anatomical Structure and Active Component Accumulation in Apocynum venetum L. (Apocynaceae) Under Saline Stress and Alkali Stress - Yanlei Zhang; Shaowei Hu; Xiaxia Wang; Jie Yue; Dongmei Chen; Mingzhi Han; Wanmin Qiao; Yifan Wang; Haixia Wang (Plants, 2025)
Soil salinization, affecting approximately 954 million hectares globally, severely impairs plant growth and agricultural productivity. Apocynum venetum L., a perennial herbaceous plant with ecological and economic value, demonstrates remarkable tolerance to saline and alkali soils. This study investigated the effects of saline (NaCl) and alkali (Na2CO3 and NaHCO3) stress on the growth, anatomical adaptations, and metabolite accumulation of A. venetum (Apocynum venetum L.). Results showed that alkali stress (100 mM Na2CO3 and 50 mM NaHCO3) inhibited growth more than saline stress (NaCl 240 mM), reducing plant height by 29.36%. Anatomical adaptations included a 40.32% increase in the root cortex-to-diameter ratio (100 mM Na2CO3 and 50 mM NaHCO3), a 101.52% enlargement of xylem vessel diameter (NaCl 240 mM), and a 68.69% thickening of phloem fiber walls in the stem (NaCl 240 mM), enhancing water absorption, salt exclusion, and structural support. Additionally, leaf palisade tissue densification (44.68% increase at NaCl 160 mM), along with epidermal and wax layer adjustments, balanced photosynthesis and water efficiency. Metabolic responses varied with stress conditions. Root soluble sugar content increased 49.28% at NaCl 160 mM. Flavonoid accumulation in roots increased 53.58% at Na2CO3 100 mM and NaHCO3 50 mM, enhancing antioxidant defense. However, chlorophyll content and photosynthetic efficiency declined with increasing stress intensity. This study emphasizes the coordinated adaptations of A. venetum, providing valuable insights for the development of salt-tolerant crops.